2015
DOI: 10.1016/j.joad.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Shock index as a mortality predictor in patients with acute polytrauma

Abstract: A B S T R A C TObjective: To evaluate whether the shock index (SI), given by the formula SI = heart rate/systolic blood pressure (HR/SBP), is useful for predicting mortality at 24 h in trauma patients admitted to the emergency department of a university hospital in Colombia. Methods: A database of trauma patients admitted between January 2013 and December 2013 was constructed; the result according to the shock index was determined, generating a dichotomous variable with two groups: Group A (SI < 0.9) and Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 20 publications
2
32
2
5
Order By: Relevance
“…SI has been previously described as a predictive metric of mortality and morbidity in specific patient populations, at cut-offs (0.7, 0.9) lower than our findings: Montoya et al evaluated more than 1000 patients in a national trauma registry, showing higher mortality in 24 hours for patients with SI>0.97; a study conducted by Reinstadler et al demonstrated that patients with recent myocardial infarction had higher myocardial damage with elevated SI above 0.62 and independently associated with major adverse cardiac events at 12 months12; Wira et al concluded that 38.6% of septic patients presenting to the ED with sustained SI elevation required vasopressors within 72 hours of ED admission, compared with 11.6% of those without a sustained SI elevation (OR 4.42; p<0.0001)23; Rady et al conducted a prospective study of 275 general adult ED patients, and concluded that SI>0.9 could identify acute critical illness and was associated with higher total admissions and intensive care unit admissions 2. These lower thresholds were unable to distinguish those at risk for admission or mortality.…”
Section: Discussioncontrasting
confidence: 57%
“…SI has been previously described as a predictive metric of mortality and morbidity in specific patient populations, at cut-offs (0.7, 0.9) lower than our findings: Montoya et al evaluated more than 1000 patients in a national trauma registry, showing higher mortality in 24 hours for patients with SI>0.97; a study conducted by Reinstadler et al demonstrated that patients with recent myocardial infarction had higher myocardial damage with elevated SI above 0.62 and independently associated with major adverse cardiac events at 12 months12; Wira et al concluded that 38.6% of septic patients presenting to the ED with sustained SI elevation required vasopressors within 72 hours of ED admission, compared with 11.6% of those without a sustained SI elevation (OR 4.42; p<0.0001)23; Rady et al conducted a prospective study of 275 general adult ED patients, and concluded that SI>0.9 could identify acute critical illness and was associated with higher total admissions and intensive care unit admissions 2. These lower thresholds were unable to distinguish those at risk for admission or mortality.…”
Section: Discussioncontrasting
confidence: 57%
“…On the other hand, patients with lower SI scores were less likely to develop hypotension but were more likely to develop hypertension and bradycardia. It is well known that a high SI predicts mortality in acute polytrauma patients [30], [31]. A more recent study showed that elevated SI predicts death in all trauma patients, but low SI values predicted death in head injured patients.…”
Section: Ketamine-induced Changes In Blood Pressure and Heart Rate Inmentioning
confidence: 99%
“…Shock index (ie, heart rate divided by systolic blood pressure) was used to demonstrate trauma injury severity among study patients; a shock index of ≥0.9 indicated a patient with severe to critical injuries. 13 Injury types were categorized by all burn injuries, penetrating injury, blunt injury, or penetrating and blunt injury. Mechanism of injury was categorized by all explosions, gunshot wound, motor vehicle crash, fall, and other.…”
Section: Injury and Intervention Categoriesmentioning
confidence: 99%